2005
DOI: 10.1016/j.devcel.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Sec15, a Component of the Exocyst, Promotes Notch Signaling during the Asymmetric Division of Drosophila Sensory Organ Precursors

Abstract: Asymmetric division of sensory organ precursors (SOPs) in Drosophila generates different cell types of the mature sensory organ. In a genetic screen designed to identify novel players in this process, we have isolated a mutation in Drosophila sec15, which encodes a component of the exocyst, an evolutionarily conserved complex implicated in intracellular vesicle transport. sec15(-) sensory organs contain extra neurons at the expense of support cells, a phenotype consistent with loss of Notch signaling. A vesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
185
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 79 publications
18
185
0
3
Order By: Relevance
“…Low levels of Rab11DN gave mild developmental defects (supplemental Figure 2B at http:/ /www.genetics.org/supplemental/) compared to control flies (supplemental Figure 2A at http://www. genetics.org/supplemental/) and high levels caused massively reduced eyes or even lethality (data not shown), confirming a previously reported cell lethality of dominant-negative Rab11 (Emery et al 2005;Jafar-Nejad et al 2005).…”
Section: Resultssupporting
confidence: 88%
“…Low levels of Rab11DN gave mild developmental defects (supplemental Figure 2B at http:/ /www.genetics.org/supplemental/) compared to control flies (supplemental Figure 2A at http://www. genetics.org/supplemental/) and high levels caused massively reduced eyes or even lethality (data not shown), confirming a previously reported cell lethality of dominant-negative Rab11 (Emery et al 2005;Jafar-Nejad et al 2005).…”
Section: Resultssupporting
confidence: 88%
“…It has been suggested that trafficking through Rab11-positive recycling endosomes ensures proper Delta activity (19). Sec15, an effector of Rab11 (20), has also been shown to be required for Delta recycling and signaling activity in signal-sending cells; however, direct evidence of ligand recycling has not been provided. Our experiments demonstrate that wt Dll1 is effectively endocytosed and recycled back to the cell surface, whereas Dll1K17R is endocytosed but not recycled.…”
Section: Several Authors Have Reported That Ubiquitination and Endocymentioning
confidence: 99%
“…Clearly, there are numerous cellular components in addition to focal adhesions, such as cytoskeletal elements, protein trafficking components and ion channels that are involved in mechanical signaling and thus may also contribute to the regulation of durotaxis [13][14][15] . Each of these components could be readily evaluated in our system using similar RNAi approaches.…”
Section: Discussionmentioning
confidence: 99%